Dampak Pembelajaran Daring Terhadap Kemampuan Anak Usia Sekolah Dasar - Gularso, Dhiniaty; Suryantari, Hadna; Rigianti, Henry Aditia; Martono (JURNAL PENDIDIKAN DASAR NUSANTARA, 2021)
This research aimed at describing the impact of online learning during COVID-19 pandemic toward primary-aged children’s ability. The research was conducted at State Elementary School of Rejodadi. The descriptive survey of quantitative method was employed to carry out this research. The data collecting technique was done by filling out an online questionnaire through Google Form. The collected data reached were 124 of 178 parents of the students from the first to sixth grade. Data analyses used were data collection, reduction, data display, and conclusion. The data analysis technique used was modus and percentage. The research reveals that online learning during COVID-19 pandemic gives impacts on children’s ability improvement and decline such as thinking, language, mathematical, technological, communication, physical, and prayer ability. The greatest improvement of children ability is on technological ability (36%) and thinking ability (17%), while the greatest decline of children ability is on thinking ability (33%) and physical ability (19%).